Antioxidative Responses of Chlorella vulgaris Under Different Growth Phases - Norhayati Yusuf; Nur Maisarah Athirah; Suhaila A (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Chlorella vulqaris is a unicellular microorganism that offers health benefits due to its concentrated antioxidant production. This microalga has received huge attention due to its natural antioxidative property as an alternative antioxidant source because of its rapid growth, easy and flexible culture. Research to date only focuses on the growth and antioxidant production in a selected growth phase, especially exponential and stationary phases; however, so far, limited reports on the production of antioxidants in all growth phases of C. vulgaris. Thus, this study determines the growth, the enzymatic (Catalase, CAT; Ascorbate Peroxidase, APX; and guaiacol peroxidase, gPOD) specific activities and the amount of the non-enzymatic antioxidants (a-tocopherol, ascorbic acid and carotenoids) of C. vulgaris in five growth phases. Chlorella vulgaris was cultured in F/2 medium at 25±2 °C under laboratory conditions. CAT specific activities were the highest at the exponential phase (1.50±0.08 units/mg protein), whereas APX and gPOD were induced at the lag phases of 37.13±4.93 units/mg protein and 1.31±0.03 units/mg protein, respectively. The amount of a-tocopherol was accumulated at the stationary phase (97.3±4.18 µg/g.fwt), whereas the highest amount of ascorbic acid (266.67±22.22 µg/g.fwt) and carotenoids (8.16±2.52 µg/g.fwt) were at the decline phase. Production of enzymatic and non-enzymatic antioxidants in the microalgae cells indicated that they efficiently scavenged reactive oxygen species (ROS) and converted them into less harmful substances. In addition, the production of these antioxidants in different growth phases can be used as a guideline to produce massive antioxidants, which can be commercialized in the food and pharmaceutical industries.